Lower numbers of FoxP3 and CCR4 co-expressing cells in an elevated subpopulation of CD4+CD25high regulatory T cells from Wegener's granulomatosis. - Klapa, S; Mueller, A; Csernok, E; Fagin, U; Klenerman, P; Holl-Ulrich, K; Gross, W; Lamprecht, P (2010)
Defects in regulatory T (Treg) cells have been implicated in the pathogenesis of chronic inflammatory and autoimmune diseases, such as Wegener's granulomatosis (WG). This study aimed at evaluating numbers, phenotype and suppressive capacity of Treg cells in WG. Peripheral blood (PB) mononuclear cells from 22 WG-patients (17 active, 5 remission) and 22 sex- and age-matched healthy controls (HC) were examined for Treg cells by flow cytometry measuring CD4, CD25, transcription factor forkhead box P3 (FoxP3), chemokine receptor CCR4 and interferon receptor I (IFNRI). Suppressive function of CD4+CD25high Treg cells from 3 WG-patients and 3 HC was analysed using a carboxyfluoresceindiacetate-succinimidylester-based in vitro proliferation assay. Endonasal biopsies of 10 WG- and 5 sinusitis-patients were investigated for CD3+FoxP3+ cells, employing double immunohistochemistry. WG-patients displayed elevated numbers of CD4+CD25med T cells and of CD4+CD25high Treg cells. CD4+ T cells of WG-patients contained higher numbers of CCR4+ cells. However, CD4+CD25high Treg cells of WG-patients exhibited decreased numbers of cells co-expressing FoxP3 and CCR4. A low but significant increase of CD4+CD25highIFNRI+ Treg cells was detected in WG-patients. 9 days following stimulation with interferon (IFN)alpha + proteinase 3 (PR3), a reduced suppression of proliferation of responder T cells was observed for WG and proliferated CD4+CD25high Treg cells still showed downregulated co-expressions of FoxP3 and CCR4. Wegener's granuloma exhibited increased numbers of CD3+FoxP3+ cells. The results indicate upregulated numbers of Treg cells in PB and nasal mucosa as well as phenotypical and functional alterations of PB Treg cells in WG, some presumably mediated through PR3 and IFN-alpha.